Newly emerging type B insulin resistance (TBIR) during treatment with eculizumab for AQP4-IgG-positive neuromyelitis optica spectrum disorder (NMOSD): fatal outcome - Doubrovinskaia, Sofia; Korporal-Kuhnke, Mirjam; Jarius, Sven; Haas, Jürgen; Wildemann, Brigitte (Journal of neurology, 2023)
Aquaporin-4 immunoglobulin G (AQP4-IgG) antibody-positive neuromyelitis optica spectrum disorders (NMOSD) are frequently associated with other autoimmune disorders, including systemic lupus erythematosus (SLE). Eculizumab (ECU) is a highly effective long-term treatment for NMOSD. However, ECU is known to increase significantly the risk of infection with encapsulated bacteria and sepsis. Recently, increased insulin resistance (IR) in patients with NMOSD has been suggested. Type B IR (TBIR) is a rare autoimmune condition often accompanying or preceding SLE. TBIR has not yet been reported in NMOSD. Objective: To report an ECU-treated patient with AQP4-IgG-positive NMOSD who developed fatal septic complications after the emergence of TBIR. Methods: Description of the clinical course over a period of 8 years. Results: A female patient was diagnosed with NMOSD at the age of 16 years. A variety of disease-modifying drugs failed to achieve sufficient disease control, resulting in severe tetraparesis. Treatment with ECU was started 6 years after NMOSD diagnosis and stabilized the disease. The patient developed TBIR 8 months after initiation of ECU therapy. Following high-dose intravenous methylprednisolone therapy for a clinical relapse and three further courses of ECU, the patient was admitted with severe pneumonia caused by the encapsulated bacterium Klebsiella pneumoniae and hypoglycemia. Despite multimodal therapy, the patient died from sepsis-related multiorgan failure 18 months after initiation of ECU. Conclusions: TBIR should be considered as differential diagnosis in patients with NMOSD presenting with disturbed glucose metabolism, irrespective of the presence of SLE. More real-world data are needed on the risk/benefit ratio of ECU treatment in patients who have co-existing autoimmune comorbidities that may compromise immune function. Strategies to mitigate the risk of serious infection in patients treated with ECU are discussed.